Formalin analysis on shrimp samples At The Surabaya I KIPM Center - Wattiheluw, Muhammad Hasan; Ningrum, Ajeng Setya (Journal of Local Therapy, 2025)
Formaldehyde, better known as formalin, is a prohibited food additive. The use of formalin in food can cause poisoning in the human body, namely acute abdominal pain accompanied by vomiting, the emergence of nervous system depression or circulatory failure. The purpose of this study was to identify the formalin content in shrimp tested at the KIPM Surabaya I Center. This study was conducted using a test kit method, namely formalin main reagent. The principle is to add liquid (reagent) to food suspected of containing formalin. The reaction between chromatophore acid and formalin produces a purple complex compound of 3,4,5,6-dibenzoxanthylium . The results of this study showed that negative shrimp samples contained formalin, indicated by the absence of color changes in the samples analyzed and compared with the positive controls that had been made.